Retinopathy of prematurity: Prevalence and risk factors - Rinawati Rohsiswatmo (Paediatrica Indonesiana, 2005)
Background Retinopathy of prematurity (ROP) is one of the ma-jor causes of infant blindness. There are several factors known asrisk factors for ROP. Recent studies show ROP as a disease ofmultifactorial origin.Objective To report the prevalence of ROP in Cipto MangunkusumoHospital, Jakarta and its relation to several risk factors.Methods A cross-sectional descriptive study was conducted fromDecember 2003-May 2005. All infants with birth weight 2500 gramsor less, or gestational age 37 weeks or less, were enrolled con-secutively and underwent the screening of ROP at 4 to 6 weeks ofchronological age or 31 to 33 weeks of postconceptional age.Result Of 73 infant who met the inclusion criteria, 26% (19 out of73 infant) had ROP in various degrees. About 36.8% (7 out of 19infants) were in stage III or more/threshold ROP. No ROP wasnoted in infants born >35 weeks of gestational age, and birth weight>2100 grams. No severe ROP was found in gestational age >34weeks and birth weight >1600 grams. None of full-term, small forgestational age infants experienced ROP. Birth weight, sepsis,apneu, asphyxia, multiple blood transfusions, and oxygen therapyfor more than 7 days were statistically significant with the develop-ment of ROP. However, using multivariate analysis, only asphyxia,multiple blood transfusions, and oxygen therapy for more than 7days were statistically significant with the development of ROP.Conclusion Screening of ROP should be performed in infantsborn 34 weeks of gestational age and/or birth weight <1600 grams.Infants with birth weight from 1600-<2100 grams need to bescreened only if supplemental oxygen is necessary or with clini-cally severe illness